Dynamics of human flight on skis: improvements in safety and fairness in ski jumping - Muller, W.; Platzer, D.; Schmolzer, B. (Journal of Biomechanics, 1996)
This study of ski jumping includes three areas of research: Wind tunnel measurements with world class athletes in various flight positions, field measurements during the World Championships in Ski Flying 1994 in Planica (Slovenia) and a highly reliable mapping of ski jumping to a computable simulation model. The results explain the effects of equipment, flight style changes, the reason for the enhanced tumbling risk and high gust sensitivity observed. Consequences can be drawn for changes to the FIS regulations, the design of jumping hills and training methods. The internationally induced anorexia of the athletes could be prohibited by a new ski length regulation. Women jumpers could become a real competitive threat.